Framing a trust game as a power game greatly affects interbrain synchronicity between trustor and trustee. (2nd November 2019) - Sun, Haoye; Verbeke, Willem. J. M. I.; Pozharliev, Rumen; Bagozzi, Richard P.; Babiloni, Fabio; Wang, Lei
ABSTRACT: We used dual electroencephalography (EEG) to measure brain activity simultaneously in pairs of trustors and trustees playing a 15-round trust game framed as a "trust game" versus a "power game". Four major findings resulted: first, earnings in each round were higher in the trust than in the power game. Second, in the trust game, reaction time for strategic deliberations was significantly longer for the trustee than the trustor. In the power game, however, the trustee took longer to think about how much money to repay, whereas the trustor took longer to think about how much money to invest. Third, prediction accuracy for the amount exchanged was higher in the trust game than in the power game. Fourth, interbrain synchronicity gauged with the phase-locking value of alpha bands in the brain – especially the frontal and central regions – was higher in the power game than in the trust game. We infer that this last finding reflects elevated mutual strategic deliberation in the power game. These behavioral and neuroscience-based findings give a better understanding of the framing effects of a trust game on the strategic deliberations of both trustor and trustee seeking to attain wealth.